Glaucoma genetics - ROJAS VARGAS, Sofia (2020)
The study had as a general objective, to validate based on a critical and structured analysis the evidence of glaucoma genetics. The research focus was qualitative, interpretive hermeneutical design; the population made up of a set of documents and treatises on the variable under study; the technique used was the documentary and content analysis, the instruments used were the content analysis matrix and bibliographic record; which analyzed the information collected. Among the main conclusions it was found that congenital glaucoma (GC) is caused by abnormal growth in terms of aqueous humor drainage formation. In addition, GC is associated with different disease subtypes such as primary open angle glaucoma. The relevance of being able to identify the genes that cause glaucoma is a first step in understanding this disease. For this reason, there are different etiologies which relate the genes involved with the development of the disease, such as the MYOC and LTBP2 genes.Keywords: glaucoma, genes, MYOC, LTBP2.